2023
DOI: 10.3389/fpls.2023.1130793
|View full text |Cite
|
Sign up to set email alerts
|

Rapid molecular assay for the evaluation of clove essential oil antifungal activity against wheat common bunt

Maria Teresa Valente,
Laura Orzali,
Giuliano Manetti
et al.

Abstract: Common bunt of durum wheat (DW), Triticum turgidum L. ssp. durum (Desf.) Husn., is caused by the two closely related fungal species belonging to Tilletia genus (Tilletiales, Exobasidiomycetes, Ustilaginomycotina): Tilletia laevis Kühn (syn. T. foetida (Wallr.) Liro.) and T. caries (DC) Tul. (syn. T. tritici (Bjerk.) G. Winter). This is one of the most devastating diseases in wheat growing areas worldwide, causing considerable yield loss and reduction of wheat grains and flour quality. For these reasons, a fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…infection on maize and wheat seeds at different doses, but the effective rates (5 × 10 3 and 5 × 10 4 ppm, respectively, for maize and wheat) had a high phytotoxicity effect [46]. Clove oil has also been tested in field trials, both as a seed soak and as coating (spray) on wheat and field peas against, respectively, Tilletia laevis [47] and Ascochyta blight complex [22], artificially inoculated on seeds, with good effectiveness, which varied from year to year. Submersion application has demonstrated a more reliable effectiveness over the years, compared to coating application.…”
Section: Activity Of Potential Basic Substances Against Fungi and Oom...mentioning
confidence: 99%
“…infection on maize and wheat seeds at different doses, but the effective rates (5 × 10 3 and 5 × 10 4 ppm, respectively, for maize and wheat) had a high phytotoxicity effect [46]. Clove oil has also been tested in field trials, both as a seed soak and as coating (spray) on wheat and field peas against, respectively, Tilletia laevis [47] and Ascochyta blight complex [22], artificially inoculated on seeds, with good effectiveness, which varied from year to year. Submersion application has demonstrated a more reliable effectiveness over the years, compared to coating application.…”
Section: Activity Of Potential Basic Substances Against Fungi and Oom...mentioning
confidence: 99%
“…EO constituents in the proper amount and way of application can numb and ease human disorders (Jamshidi-Kia et al, 2018). EOs have diverse properties such as antifungal (Valente et al, 2023), immune boosting (Sandner et al, 2020), cytotoxicity (Pereira et al, 2017), antioxidant (Nadeem et al, 2022), and antibacterial activities (Wu et al, 2019). Researchers have recently become interested in using Spearmint essential oil (SEO) to preserve foodstuffs, including meat (Shahbazi et al, 2018) and fruit (Yan et al, 2021), rather than occasionally environmentally unfriendly materials.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many previously developed assays are low-throughput, and international protocols involve time-consuming processes like morphological observations and spore isolation (Valente et al, 2019). A series of DNAbased methods have attempted to distinguish teliospores of Tilletia species from seeds or soil samples, which serve as the primary source of pathogen spread (Eibel et al, 2005;Chen et al, 2016;Valente et al, 2023). In earlier studies, PCR based techniques such as RAPD primer-mediated asymmetric polymerase chain reaction (Yuan et al, 2009), sequencecharacterized amplified region (Liu et al, 2009;Gao et al, 2010), repetitive element polymerase chain reaction (Vesna et al, 2011), inter-simple sequence repeat (Gao et al, 2011), amplified fragment length polymorphism (Zhang et al, 2012), and sequence characterized amplified region (Ren et al, 2022a;Xu et al, 2022) have been successfully demonstrated for the identification of Tilletia species.…”
Section: Introductionmentioning
confidence: 99%